Analysis on Students’ Perspective Toward Academic, Career Aspirations and Destinations After SPM in Muar, Johor - Nik Izan, Nik Mufidah Hasanah; Mohd Razali, Siti Noor Asyikin (Enhanced Knowledge in Sciences and Technology, 2026)
This study examines upper secondary school students’ views on their higher education and career goals, as well as the variables that affect their planned career paths after completing the Sijil Pelajaran Malaysia (SPM). Many students find it challenging to make accurate decisions due to the influence of circumstances, social, and personal factors, even though many educational and professional opportunities are available after SPM. It is crucial to understand these difficulties to help students make better-informed, more suitable decisions after SPM. A structured questionnaire was the primary data collection tool in a quantitative study design. A survey method was applied to gather information from secondary school students. Students’ after-SPM plans and demographic characteristics were summarised using descriptive statistics. To investigate variations in ambitions and influencing factors across demographic groups, the Mann-Whitney U test and the Kruskal-Wallis H test were used. To find correlations between demographic factors and students’ post-SPM choices, the chi-square test of independence was used. To determine the fundamental factors influencing students’ post-SPM decision-making, an exploratory factor analysis (EFA) was conducted. The results show that the majority of students (70.7%) intend to pursue further education after SPM, with work coming in second and entrepreneurship the least prevalent choice. Students’ academic or career goals and after SPM decisions were not substantially influenced by age, gender, household wealth, or religion (p > 0.05). The academic stream had a substantial impact on the factors influencing students’ decisions (p < 0.05) but was not associated with career goals (p > 0.05). Self-efficacy and goal clarity, financial limitations, social influence, knowledge access, and media and environmental impacts were identified as the five main determinants. In general, contextual and personal factors influence after SPM decisions more than demographic traits.